Anaphylactic Reaction to Anakinra in a Rheumatoid Arthritis Patient Intolerant to Multiple Nonbiologic and Biologic Disease-Modifying Antirheumatic Drugs - Desai, Ditina (2009)
OBJECTIVE: To report a case of probable anaphylaxis due to anakinra in a patient with rheumatoid arthritis and multiple drug allergies. CASE SUMMARY: A 46-year-old Indian female with rheumatoid arthritis demonstrated distinct adverse reactions to all commercially available anti–tumor necrosis factor therapies, sulfasalazine, and hydroxychloroquine. Over a 4-year period her disease remained active during therapy with methotrexate and prednisone. Biologics were added sequentially, with development of intolerable reactions, first to infliximab (urticarial rash, infusion reactions) after 3 doses, and then to etanercept (autoantibodies, worsening Raynaud’s phenomenon, digital microinfarcts) after 1 year. Following 2 months of daily injections of anakinra, she experienced an immediate immunoglobulin E–mediated anaphylactic reaction within 20 minutes of an injection, as evidenced by positive testing to both anakinra and histamine with the skin prick method. The patient subsequently started adalimumab therapy, which was discontinued after the fourth dose due to the development of generalized hives. DISCUSSION: The Naranjo probability scale demonstrated a probable relationship between anaphylaxis and anakinra in this patient. Although cases of anakinra-related hypersensitivity have been reported in patients in which therapy was interrupted and then reintroduced, to our knowledge, this is the first report of anaphylaxis with continuous therapy. CONCLUSIONS: This unusual case of a patient with multiple drug allergies presents a difficult clinical scenario, which was unsuccessfully managed with multiple biologic therapies on a trial-and-error basis. In the future, pharmacogenetics may help to better identify individuals at risk for multiple drug reactions and preclude unnecessary exposure to potentially harmful therapeutic options in similar patients.